1996
DOI: 10.1103/physrevb.53.1076
|View full text |Cite
|
Sign up to set email alerts
|

Modifications of the electronic and magnetic properties of ultrathin Ni/Cu(100) films induced by stepwise oxidation

Abstract: We report near-edge x-ray-absorption fine-structure ͑NEXAFS͒ and magnetic circular x-ray dichroism ͑MCXD͒ measurements of 4-ML Ni films grown on Cu͑100͒. The films were exposed to oxygen which then adsorbed in different adsorption states. The changes in the density of states as probed at the Ni L 2,3 edges, the oxygen K edge, as well as the magnetic response of the sample are investigated simultaneously for the various adsorption states that range from O 2 /Ni at 38 K to an ultrathin film of NiO. The NEXAFS sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 28 publications
2
20
0
Order By: Relevance
“…This is because the sharp structure located at 530 eV exactly originates from these hybridized 2p z 3d states. 23 Furthermore, the excellent statistics even allow for the identification of a small asymmetry in the O XMCD-i.e., the small positive contribution located at about 532 eV.…”
Section: Resultsmentioning
confidence: 99%
“…This is because the sharp structure located at 530 eV exactly originates from these hybridized 2p z 3d states. 23 Furthermore, the excellent statistics even allow for the identification of a small asymmetry in the O XMCD-i.e., the small positive contribution located at about 532 eV.…”
Section: Resultsmentioning
confidence: 99%
“…19 The worst contamination levels recorded in any sample by AES indicated a 4% oxygen component for the completed 600-Å Cu buffer and Ni layer. May has found that 0.5 ML of atomic oxygen suppresses the magnetization corresponding to one layer of Ni, and for 1.5 ML no ferromagnetic response from a 4-ML Ni film was found at 38 K. 33 Tischer et al also find effects of similar magnitudes in their ultrathin Ni films. 34 The information depth of the Auger was approximately 10 Å.…”
Section: Contamination Intermixing and Roughnessmentioning
confidence: 95%
“…For the comparatively weak ferromagnet nickel, the oxygen 22 and hydrogen 23 seriously affect the magnetization. The recent calculations 24 show, in accord with experiments, that CO kills the magnetization at the surface of Ni clusters.…”
Section: Introductionmentioning
confidence: 99%